Skeletal muscle mass to visceral fat area ratio as a predictor of NAFLD in lean and overweight men and women with effect modification by sex. Issue 9 (3rd May 2022) - Cho, Yoosun; Chang, Yoosoo; Ryu, Seungho; Jung, Hyun‐Suk; Kim, Chan‐won; Oh, Hyungseok; Kim, Mi Kyung; Sohn, Won; Shin, Hocheol; Wild, Sarah H.; Byrne, Christopher D.
Abstract: The effect of sarcopenic visceral obesity on the risk of nonalcoholic fatty liver disease (NAFLD) is uncertain. We investigated (a) whether the skeletal muscle mass to visceral fat area ratio (SV ratio), as a measure of sarcopenic visceral obesity, is a risk factor for NAFLD; and (b) whether the SV ratio adds to conventional adiposity measures to improve prediction of incident NAFLD. Adults without NAFLD ( n  = 151, 017) were followed up for a median of 3.7 years. Hepatic steatosis was measured using ultrasonography, and liver fibrosis scores were estimated using the Fibrosis‐4 index (FIB‐4) and the NAFLD Fibrosis Score (NFS). Cox proportional hazards models were used to determine sex‐specific adjusted hazard ratios (aHRs) (95% confidence intervals [CIs]). The incremental predictive performance was assessed using the area under the receiver operating characteristic curve, net reclassification improvement, and integrated discrimination improvement. Multivariable aHRs (95% CIs) for incident NAFLD comparing the lowest versus the highest quintile of SV ratio were 3.77 (3.56–3.99) for men and 11.69 (10.46–13.06) for women ( p –interaction by sex < 0.001). For incident NAFLD with intermediate/high FIB‐4, aHRs were 2.83 (2.19–3.64) for men and 7.96 (3.85–16.44) for women (similar results were obtained for NFS). Associations remained significant even after adjustment for body mass index, waist circumference, and time‐varying covariates. These associations were also more pronounced in nonobese than obese participants ( p –interaction < 0.001). The addition of SV ratio to conventional adiposity measures modestly improved risk prediction for incident NAFLD. SV ratio was inversely associated with risk of developing NAFLD, with effect modification by sex and obesity. Conclusion : Low SV ratio is a complementary index to conventional adiposity measures in the evaluation of NAFLD risk. Abstract : Skeletal muscle mass to visceral fat area ratio (SV ratio) measures a sarcopenic visceral obesity. Low SV ratio was a strong and independent risk factor for developing NAFLD. Associations were most pronounced in women and in lean individuals.image